STUDI KONDISI FISIK RUMAH TINGGAL PERMUKIMAN MASYARAKAT BERPENGHASILAN RENDAH DI KAWASAN PUSAT KOTA PALU - Mulyati, Ahda (MEKTEK, 2008)
Low Income Society dwelling forms as city villages , generally placed in center city area, high population density, without enough yard also lack physic infrastructure environment. That function of housing for shelter, settle, on going process, social interaction, and asset for life. Indicated that resident using rooms in their environment dwelling as maximal as they can to dwelled activity, social interact and working. Open rooms is the most dominant area used to the activities which stand receding livings. Because lack of area, living house build appropriate with citizen needs and ability without considering to safety factor, healthy and dwelling environmental condition which suitable to settle. To develop the housing use material and construction non standard, but ten percent housing used material and construction with standard quality for technic